Analisis Program Pembinaan Seni Baca Al-Qur’an pada LPTQ Provinsi Sumatera Utara - Tantri Rizky Alviani; Rizky Febriansyah Sinaga; Rajab Al Fathin Muhammad Nasution; Sri Ahadah Nuril Fajar; Frasiska Sari Juwita; Shelma Shelma; Agung Julian Siregar; Muhammad Hidayat (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
The development of the art of reading the Qur'an (tilawah) plays an important role in maintaining the Qur'anic tradition in North Sumatra, especially since this region is one of the regions actively involved in organizing the Musabaqah Tilawatil Qur'an (MTQ). However, the quality of development at the district/city level is not evenly distributed, thus impacting the ability of qari and qari'ah to achieve professional tilawah standards. This study aims to analyze the development program of the art of reading the Qur'an implemented by the LPTQ of North Sumatra Province, including the form of activities, implementation mechanisms, and its effectiveness in improving participant competence. The research method uses a descriptive qualitative approach through direct observation of development activities, analysis of official institutional documents, and supporting documentation related to the training process and implementation of the MTQ. The results show that the LPTQ development program includes routine development, Training Center (TC), and Training of Trainers (ToT), each of which has a different contribution to improving participant abilities. Routine development serves as a foundation, TC has proven to be most effective in maturing participants before the MTQ, while ToT plays a role in increasing the capacity of trainers in the region. However, the program's overall effectiveness remains hampered by a limited number of expert trainers, limited facilities, regional disparities, and low interest among young people in the art of tilawah. This study concludes that training needs to be strengthened through equitable distribution of trainers, increased program intensity, utilization of digital media, and more stable budget support to achieve sustainable tilawah training in North Sumatra.